Soft Skills Academy - Preparing The Young Generation People For The Workplace - Hanafiah, Hally (Lentera Ilmu Madani, 2024)
This community service program aims to improve the work readiness of the younger generation, especially students in grades X and XI of SMK Industri Jababeka, in facing the challenges of an increasingly competitive world of work. This activity is designed to equip participants with essential soft skills, including effective communication, leadership, time management, teamwork, and problem solving, in order to increase their competitiveness and confidence in entering the professional world. The program implementation method includes the preparation stage in the form of a participant needs survey and preparation of training modules; the implementation stage through interactive material delivery, discussions, case study simulations, and teamwork in simulation projects; and the evaluation stage through satisfaction surveys and preparation of activity reports. This activity was attended by 46 participants, with the results showing that 85% of participants experienced a significant increase in understanding and soft skills, reflected in their ability to create a curriculum vitae (CV), carry out job interview simulations, and show improved communication skills, teamwork, and time management. This soft skills training program proved effective in improving participants' work readiness and is expected to become a sustainable model for competent human resource development in other regions.